The Effect of HCl Activator on PET Adsorbent to Reduce Phosphate Content in Laundry Waste - Lutfi Wahidatur Rizky; Iskandar Zulkarnain; Ismadi Raharjo; Yeni Ria Wulandari (Program studi Teknik Kimia UNS, 2024)
Plastic waste is waste that cannot be decomposed so it will cause serious problems to the environment. The National Waste Management Information System (SIPSN) reported that in 2020 plastic waste was found to be 17.2% of the total waste collected. Several types of plastic can become porous charcoal through the heating process in a furnace so that it can be used as an adsorbent for liquid waste from the laundry industry. Laundry liquid waste containing excess phosphate will disrupt the environment such as eutrophication. This research aims to determine the effect of the HCl activator on carbon from polyethylene terephthalate (PET) plastic bottle waste to reduce phosphate levels in liquid laundry waste. This research uses varying concentrations of HCl as a carbon activator, namely 1M, 5M, and 10M. The activated carbon is added to the liquid laundry waste and stirred at a speed of 100 rpm. Phosphate content analysis was carried out using a spectrophotometer in liquid laundry waste before and after the adsorption process and BET (Brunauer-Emmet-Teller) analysis on activated carbon with activator HCl 10 M. The greatest decrease in phosphate levels was 10 M HCl concentration of 52.87%, with a carbon surface area of 203.1222 m²/g and a particle size of 29.53 nm. The adsorption capacity of activated carbon with a 10 M activator is 0.1499 mg/g. Keywords:PET, Adsorbent, HCl, Laundry Waste, Phosphate